Estudo do comportamento de argamassas de revestimento com areia de britagem da região metropolitana de Fortaleza - Diógenes, Afrânia Gadelha (2016)
Natural sand is a mineral resource widely used in the construction industry for the production of mortars and concrete. However, obtaining this mineral resource is becoming increasingly difficult due to the depletion of deposits close to large consumer centers and the growing environmental constraints. Because of this, the crushing sand is an alternative to the shortage of natural sand. This study aims to assess the technical feasibility of riverbed sand replacement by crushing sand in the production of coating mortars, and to evaluate the influence of the content of powdery material and water in the properties of mortars in fresh and hardened. The methodology consists in making mixed mortar coating with 3 types of crushing sand from quarries in the Metropolitan Region of Fortaleza (RMF), making 4 replacement percentages by volume of natural sand for sand crushing: 25%, 50 %, 75% and 100%, and more a reference, 0% crushed sand, getting a total of 13 strokes. Mortars were produced according to requirements of the standard NBR 13276: 2005 and their performance was analyzed in the fresh state as the amount of water needed for a fixed consistency (245 ± 10 mm) on the table, the mass density, the content of incorporated air and water retention. Furthermore, their behavior in the hardened state was investigated: bulk density, elastic modulus, compressive strength and tension in flexion, as well as adhesion and tensile cracking. For data analysis, we used the variance analysis (ANOVA) and verified the viability of the use of crushed sand to replace natural sand in a 25% content for making mortar coating that generally, showed high workability with lower water consumption and an increase in the values of mechanical resistance.